Guidelines for Reporting Novel mecA Gene Homologues - Ito, T.; Hiramatsu, K.; Tomasz, A.; de Lencastre, H.; Perreten, V.; Holden, M.; Coleman, D.; Goering, R.; Giffard, P.; Skov, R.; Zhang, K.; Westh, H.; et al. (American Society for Microbiology, 2012)
Methicillin-resistant staphylococci are disseminated all over the world and are frequent causes of health care- and community-associated infections. Methicillin-resistant strains typically carry the acquired mecA gene that encodes a low-affinity penicillin-binding protein (PBP), designated PBP2a or PBP2′. In most strains, mecA is part of a chromosomally integrated mobile genetic element called staphylococcal cassette chromosome mec (SCCmec). The mecA gene is widely disseminated among Staphylococcus aureus and other staphylococcal species, and its expression is essential for the methicillin-resistant phenotype. Recently, mecA gene homologues that are only distantly related to mecA have been identified in the genomes of staphylococci and some related bacterial species (Table 1). So far, four groups of mecA homologues have been described based on their degree of homology to the earliest identified mecA gene. We believe that this diversity warrants a new naming system based on phylogenetic principles which can also serve as a guideline for the reporting of additional novel mecA homologues that may be identified in the future.